2022
DOI: 10.3390/toxics10020045
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Methodology for Quantitation and Site-Specific Mapping the Location of DNA Adducts

Abstract: Formation of DNA adducts is a key event for a genotoxic mode of action, and their presence is often used as a surrogate for mutation and increased cancer risk. Interest in DNA adducts are twofold: first, to demonstrate exposure, and second, to link DNA adduct location to subsequent mutations or altered gene regulation. Methods have been established to quantitate DNA adducts with high chemical specificity and to visualize the location of DNA adducts, and elegant bio-analytical methods have been devised utilizin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…We inferred the RNA modifications of dRNA sequences using our developed epitranscriptional/epigenomical landscape inferring from glitches of ONT signals (ELIGOS) software ( Nookaew et al, 2020 ; Jenjaroenpun et al, 2021 ; Boysen and Nookaew, 2022 ) with two approaches. First, profiling of RNA modifications of the individual growth condition was performed by comparing the error at specific base (ESB) with the RNA background error model (rBEM).…”
Section: Methodsmentioning
confidence: 99%
“…We inferred the RNA modifications of dRNA sequences using our developed epitranscriptional/epigenomical landscape inferring from glitches of ONT signals (ELIGOS) software ( Nookaew et al, 2020 ; Jenjaroenpun et al, 2021 ; Boysen and Nookaew, 2022 ) with two approaches. First, profiling of RNA modifications of the individual growth condition was performed by comparing the error at specific base (ESB) with the RNA background error model (rBEM).…”
Section: Methodsmentioning
confidence: 99%
“…Other methods such as DIIP assay or CPD‐seq, XR‐seq, damage‐seq, cisplatin‐seq, and tXR‐seq are also used for similar purposes [101–106] . While seemingly promising, these methods possess several limitations, such as limited enzyme specificities for DNA adduct identification, short fragments alignment‐related issues during post‐sequencing data analysis, and being confined to some adduct types due to the non‐availability of antibodies against all known DNA adducts [107] . These limitations suggest the need for developing alternative approaches.…”
Section: Linking Adducts Chemistry To Dna Sitesmentioning
confidence: 99%
“…We recently demonstrated that Oxford Nanopore Technologies (ONT), which is a third-generation sequencing platform can detect nucleic acid modifications ( Jenjaroenpun et al, 2020 ; Nookaew et al, 2020 ; Boysen and Nookaew, 2022 ). The ONT platform sequences native DNA and RNA, with nucleotide bases having their own electrical signal known as a “squiggle.” The ONT platform can detect modified bases because of the difference in the squiggle between modified and unmodified bases ( Xu and Seki, 2020 ).…”
Section: Introductionmentioning
confidence: 99%